التعليم القرآني في بلدة تغزوت بوادي سوف خلال عهد الاحتلال الفرنسي 1882- 1962 - سالم الحبيب (University Of Eloued جامعة الوادي, 2023)
تعتبر بلدة تغزوت من أقدم الحواضر التاريخية في وادي سوف, وذلك باستقرار سكانها الأصليين الأوائل في منطقة جُلهمة ( هي المدينة والتسمية القديمة لتغزوت والواقعة شمال غرب تغزوت الحالية) والتي تأكد على أصالة وعراقة هذه البلدة, وقد اجتهد هؤلاء السكان في تشييد المنازل والمساجد فيها, هذه الأخيرة التي كانت إلى جانب الزوايا والكتاتيب تمثل قلاعا حصينة لتعليم القرآن الكريم لأطفال القرية منذ الفتح الإسلامي لبلاد المغرب وإلى غاية الاحتلال الفرنسي لمنطقة وادي سوف (1882- 1962) وهي الحقبة التاريخية التي سنسلط الضوء فيها على مناهج وطرق التعليم القرآني في بلدة تغزوت باعتبار أن عهد الاحتلال الفرنسي كان عهد طمس لمبادئ الهوية الوطنية والإسلامية محاولين في هذه الورقة التنقيب عن أبرز جهود رجال التعليم القرآني والمساجد التي عملوا فيها. The town of Taghzout is considered one of the oldest historical cities in Oued Souf , due to the settlement of its first indigenous inhabitants in Jolhama's area (it is the city and the old name of Taghzout, where is located in the northwest of present-day Taghzout), which confirms the authenticity and nobility of this town, and these residents have worked hard to build houses and mosques in it. The last, besides the Zawaya and Katateeb, represented fortified fortresses for teaching the Holy Qur’an to the children of the village since the Islamic conquest of the Maghreb until the French occupation of the Oued Souf (1882-1962), which is the historical period in which we will shed light on the curricula and methods of Qur’anic education in the town of Taghzout, considering that the era of The French occupation was an era of obliteration of the principles of national and Islamic identity, trying in this paper to explore the most prominent efforts of Quranic educators and mosques in where they were worked.
Keywords: تغزوت; التعليم القرآني; المساجد; Taghzout; Quranic education; mosques